Legalización de uniones consensuales en México - Pebley, Anne R.; Goldman, Noreen (El Colegio de México A.C., 1986)
The purpose of this paper is to describe legalization within the context of the Mexican marriage pattern. The sources utilized in the research were the Mexican Fertility Survey of 1976 and the pecfal survey of 1969. The paper examines the characteristics of women who originally entered into non-legalized unions and those who entered into legal marriages; the frequency and timing of legalization in the case of unions and their relationship to fertility, as well as the stability resulting from legalized unions in comparison with legal marriages where prior cohabitation did not exist. The findings indicate that while unions are quite common among Mexican women, a good number of these relationships are later legalized. The frequency of legalization in rural and urban areas is similar, although unions are more common in the rural areas. This study corroborates the findings of an earlier analysis to the effect that pregnancy is not a factor which precipitates legalization. Finally, it was found that there is no difference in the stability of couples who have or have not had prior cohabitation.